Analisis Kebijakan Mutasi Asn Pasca Pilkada Berdasarkan Undang-Undang Nomor 10 Tahun 2016 Perspektif Fiqh Siyasah - Ipandang Ipandang; Irma Irayanti; Kamaruddin Kamaruddin; Aris Nur Qadar Ar-Razak; Mislu Zaini (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Mutations for the State Civil Apparatus are commonplace in an organization or government agency. However, the mutation policy that was carried out after the Pilkada in Muna Regency was considered a technical, administrative and political phenomenon. The aims of this study are (1) to identify the mechanism for post-election mutations in Muna Regency; (2) Identifying the legal implications of the ASN mutation policy after the Regional Head Election in the Muna Regency government based on Article 72 paragraph (2) of Law number 10 of 2016 (3) Identifying Fiqh Siyasah's views regarding the ASN Mutation Policy after the Regional Head Election in Regional Government Muna District. The results of this study indicate that (1) In practice, the mutations carried out after the Regional Head Election are based on the needs of employees in a State Civil Apparatus employee office, this is done for the distribution of State Civil Apparatus Employees evenly and fairly; (2) Implementation of mutations according to the law, mutations are carried out on functional officials while what is meant in Article 72 of Law number 10 of 2016 are structural officials and functional officials who get additional tasks; (3 Mutation policy in Fiqh Siyasah can be done and occurred during the time of the Prophet Muhammad until the Caliphate of Umar Bin Al-Khattab.